THE EFFECT OF EDUCATION WITH POSTER MEDIA ON INCREASING KNOWLEDGE OF HAND WASHING FAMILY OF INPATIENTS MEURAXA REGIONAL HOSPITAL, BANDA ACEH - Eridha Putra; Rahilmiati Rahilmiati; Rehmaita Malem (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Hand washing is a process that mechanically removes dirt from the skin of the hands using soap and water. The aim of the research is to determine the effect of education using poster media on increasing hand washing knowledge in families of inpatients at Meuraxa Hospital, Banda Aceh. Quantitative research design with a quasi-experimental design approach using the Pre-experimental method with one group pre-test post-test with family research subjects accompanying patients at Meuraxa Regional Hospital, Banda Aceh. The sampling technique used accidental sampling based on chance with a total of 94 people. The results of the level of knowledge before being given counseling were almost half sufficient, amounting to 41 (43.6%) and the total level of knowledge before being given counseling was mostly poor, amounting to 53 (56.4%) and the level of knowledge after being given counseling was mostly good, amounting to 57 (60.6%) and the level of knowledge after almost half of those providing counseling, amounting to 37 (39.4%) respondents. This research shows a significant p-value (0.000 < 0.05). Based on the results of the research above, it can be concluded that there is an increasing influence before and after providing counseling using poster media to the patient's family. This counseling is able to increase accuracy in washing hands according to the correct flow and procedures, this is due to clearer teaching. However, a small number of respondents have washed their hands but not properly, due to the age factor where respondents are aged 50-65 years, which is the beginning of old age, which means reduced ability to catch, so repeated explanations must be given . It is recommended for the patient's family to pay attention to procedures and steps for washing hands properly because this is the main thing to break the chain of spread of bacteria when in the hospital environment.